Analisis Implementasi Kurikulum K-13 di Madrasah - Ishomuddin, Cholid; Maula, Rofikatul (AFKARINA: Jurnal Pendidikan Agama Islam, 2022)
This research focuses on the implementation of the 2013 Curriculum at Madrasah Aliyah Bahrul Ulum. The purpose of this research is to analyze the implementation of the 2013 curriculum and identify the factors that influence the implementation of the curriculum. The method used in this study is a qualitative descriptive method with three main instruments; observation, interviews and documentation used to collect data. The results we got from research at the Madrasah Aliyah Bahrul Ulum in its implementation went through 3 stages namely facilitation, socialization, and teacher preparation. From the results of the study it was concluded that all components including government, schools, teachers, parents, students, and stake holders must be interested in and support the implementation of K 13 Madrasah Aliyah Bahrul Ulum.